Factors Influencing Career Choice: A Comparison between Undergraduates from Rural and Private Secondary Schools - Vunandlala, Malibongwe Cyprian (University of the Witwatersrand, Johannesburg, 2024)
This research study focused on the factors that influenced the career decision-making process of university undergraduate students whilst they were operating at the secondary school level. This qualitative study compared the factors that influenced the career choices of undergraduates from rural secondary schools to undergraduates from private secondary schools. The aim of this research was to generate a clearer and more in-depth narrative, whilst enhancing the understanding of the similarities and differences in these factors, when comparing rural and private secondary schools. Career choice is a very important life decision in one’s long-term future and overall sense of fulfilment (Rousseau & Venter, 2009). For this reason, and given the rapidly changing landscape of the world of work, it is essential that an understanding of the factors that influence these career choice decisions continue to be developed. This study employed an exploratory, qualitative, cross-sectional research design. The sampling method that was used for data collection was non-probability in nature, whereby the purposive sampling technique was employed. A sample of six students from each of the two groups of students (rural and private) was collected (total sample size = 12). A Semi structured interview guide based on the Systems Theory Framework was developed and utilised by the researcher. In depth interviews were audio-recorded and transcribed and analysed using thematic analysis proposed by Braun and Clarke (2006). This research found that the career choice of secondary school students is influenced by a wide range of factors, highlighting key differences and commonalities between rural and private secondary school students. The findings revealed that students from rural schools often face significant socioeconomic challenges, including financial constraints, limited access to career counselling, and a lack of exposure to diverse career opportunities. Conversely, undergraduates from private schools tended to have greater access to resources such as career guidance programs, mentorship opportunities, and role models, which broadened their career aspirations and enabled them to explore a wider range of professions. Furthermore, this research paper also emphasised the significance of taking a proactive approach in seeking additional career information, reinforcing that students are not merely passive subjects of their circumstances.
A research project submitted in partial fulfilment of the requirements for the degree of Master of Arts by Coursework and Research Report in the field of Industrial/Organisational Psychology, to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: Autobiography; Biography; Lifewriting; Memoir; Celebrities; South Africa; Black; UCTD; SDG-4: Quality education; SDG-10: Reduced inequalities